Synthesis, Characterization, and Evaluation of Antimicrobial Efficacy of Reduced Graphene-ZnO-Copper Nanocomplex - Varish Ahmad; Mohammad Omaish Ansari (MDPI AG, 2023)
The prevalence of antibiotic-resistant diseases drives a constant hunt for new substitutes. Metal-containing inorganic nanoparticles have broad-spectrum antimicrobial potential to kill Gram-negative and Gram-positive bacteria. In this investigation, reduced graphene oxide-coated zinc oxide-copper (rGO@ZnO-Cu) nanocomposite was prepared by anchoring Cu over ZnO nanorods followed by coating with graphene oxide (GO) and subsequent reduction of GO to rGO. The synthesized nanocomposite was characterized by scanning electron microscopy, transmission electron microscopy, elemental analysis, and elemental mapping. Morphologically, ZnO-Cu showed big, irregular rods, rectangular and spherical-shaped ZnO, and anchored clusters of aggregated Cu particles. The Cu aggregates are spread uniformly throughout the network. Most of the ZnO particles were partially covered with Cu aggregates, while some of the ZnO was fully covered with Cu. In the case of rGO@ZnO-Cu, a few layered rGO sheets were observed on the surface as well as deeply embedded inside the network of ZnO-Cu. The rGO@ZnO-Cu complex exhibited antimicrobial activity against Gram-positive and Gram-negative bacteria; however, it was more effective on Staphylococcus aureus than Escherichia coli. Thus, rGO@ZnO-Cu nanocomposites could be an effective alternative against Gram-positive and Gram-negative bacterial pathogens.